The brutality of war: A perspective on the actions of Olaf Bergh’s black scouts at Smaldeel during the South African War (1899-1902) - Labuschagne, Pieter (Scientia Militaria - South African Journal of Military Studies, 2017)
The intensity of the South African War (1899-1902) escalated sharply during the guerrilla phase in the rural areas outside the conventional theatre of operations. The conflict, which already resembled a total war, had a devastating destabilizing effect on the socio-economic stability and internal security in the rural areas of the two Boer Republics. The resulting lack of internal or domestic security in the rural areas eroded internal control by the Boer community and giving rise to a power vacuum. This development put the black population in the position to challenge white rule. This challenge took the form of armed black units under the command of either ‘joiners’ or British officers that started to operate in the unregulated and unsecured space. The black units committed tasks in the power vacuum that varied from spying to assisting the British forces to transport Boer women and children from their farms to concentration camps. In some cases armed blacks also operated as a military unit to challenge small pockets of Boers. The Boer population reacted with bitterness against these armed units. The expressed animosity even surpassed the adverse feelings they had for the British. The aim of the article is to investigate this phenomenon, with specific focus on the actions of Olaf Bergh in the Free State, who commanded a Winburg unit consisting of 500 armed blacks. Bergh’s actions at Smaldeel station in the central Free State caused anger and bitterness that lingered for decades after the War. The focus of the article is to explain why the reaction against Bergh and his black unit was so strong and bitter, and also disproportionally stronger than the general feeling of animosity toward the British.